Study on Hot Deformation Behavior of 7085 Aluminum Alloy during Backward Extrusion Process. (29th March 2015) - Mei, R. B.; Du, Y. X.; Bao, L.; Zhang, X. Y.; Zhang, B.; Zhou, Z. J.
Abstract : Compression test was carried out and the true stress-strain curves were obtained from the hot compression of 7085 alloy. A numerical simulation on the deformation behavior of 7085 aluminum alloy during the backward extrusion was also performed by finite element method. The results show that dynamic recrystallization occurs in the hot compression of 7085 alloy and the peak stress reaches higher values as the strain rate increases and deformation temperature decreases. The backward extrusion processes include contact deformation, initial deformation, and steady deformation. Severe plastic deformation of shear and compression occurs when the metal flowed into the channel between fillet of punch and wall of die so that the grain size can be refined by backward extrusion. The deformation in the region of top of wall is too small to meet the mechanical properties of requirements and the metal usually needs to be trimmed. The experiments with the same parameters as simulation had been carried out and the experimental cup after extrusion has better quality.